Ethological isolation and mating experience in Drosophila paulistorum. - O'Hara, E (1976)
With few exceptions, previously published experiments documenting ethological isolation between Drosophila populations have used young virgin females. We have observed directly females of Drosophila paulistorum semispecies in choice experiments with both homogamic and heterogamic males. Aged females' sexual selection did not differ from that of young females. Previous heterogamic copulatory experience did not change the degree of sexual isolation; however, females with homogamic copulatory experience showed a significantly higher preference for homogamic males.